Определение силовых характеристик неустановившегося поворота шарнирно сочлененной машины с тремя осями - Гурвич, Ю. А.; Третинников, Д. Л.; Петровский, А. Л. (БНТУ, 2011)
In the article have been considered a unsteady turn of hinged machine. The research is topical because the up-to-date state of open-cut method progress of mineral product on majority of operating enterprise is characterized by open cast mine deepening, by load distance increasing and by angle of ascent of track rising.